Correction: Functional and Anatomical Outcomes of Faricimab in Previously Treated Wet Age-Related Macular Degeneration: Systematic Review and Pooled Analysis. - Khodor, Ali.; Caranfa, Jonathan T; Nanda, Tavish.; Ruiz-Lozano, Raul E; Quiroga-Garza, Manuel E; Choi, Stephanie.; Chehab, Ali.; Ramos-Dávila, Eugenia M; Heier, Jeffrey S; Shah, Chirag P; Witkin, Andre J (Tufts University. Tisch Library., 2025)
Springer Open.